Recent Advances in Decarboxylative Reactions of Alkynoic Acids - Idris, Muhammad Aliyu; Lee, Sunwoo (Synthesis, 2020)
Alkynoic acids have been widely employed as alkyne and alkene sources in decarboxylative reactions. Alkynoic acid coupling leads to the formation of direct coupling products and cyclized products through sequential reactions. Moreover, homocoupling and multicomponent reactions have been developed. The decarboxylative addition of alkynoic acids generates the corresponding alkene products. A number of synthetic methods are utilized for the preparation of arylpropynoic acids including the Sonogashira coupling and the carboxylation of terminal alkynes. Recently, the use of decarboxylative halogenations has also been reported. This review covers decarboxylative reactions of alkynoic acids reported between 2013 and 2019; further, it is divided into several sections according to the type of reaction.1 Introduction2 Direct Coupling3 Sequential Reactions4 Homocoupling5 Multicomponent Reactions6 Addition7 Halogenations8 Synthesis of Alkynoic Acids9 Conclusion
Keywords: alkynoic acid; decarboxylative coupling; propynoic acid; transition-metal catalyst; alkyne